The essential oils of Lantana camara L. occurring in North Brazil - Silva, Milton Hélio L da; Andrade, Eloísa Helena de Aguiar; Zoghbi, Maria das Graças Bichara; Luz, Arnaldo Iran R.; Silva, João Domingos da; Maia, José Guilherme Soares (Flavour and Fragrance Journal, 1999)
The essential oils of aerial parts of three samples of Lantana camara L. collected at different places in the Amazon Region were obtained by hydrodistillation and analysed by GC-MS. The main constituents found in the oil of leaves and thin branches of a specimen collect in the State of Amapia (sample A) were limonene (16.5%), α-phellandrene (16.4%), germacrene-D (13.2%), β-caryophyllene (10.8%) and sabinene (8.9%). The major components identified in the oil of leaves and thin branches of a specimen collected in the State of Roraima (sample B) were germacrene-D (28.4%), germacrene-B (9.1%) and β-caryophyllene (5.6%). The specimen collected in the State of Para (sample C) furnished oils from leaves plus thin branches and flowers, separately. Both were dominated by γ-curcumene + ar-curcumene (27.6%; 31.9%), α-zingiberene (19.2%; 15.5%) and α-humulene (10.7%; 9.5%), respectively.
Keywords: Caryophyllene; Essential Oil; Humulene; Limonene; Plant Extract; Sabinene; Chemical Composition; Distillation; Gas Chromatography; Mass Spectrometry; Plant Leaf; Lantana Camara